Protective Effect on Mortality of Active Commuting to Work: A Systematic Review and Meta-analysis - Dutheil, Frédéric; Pélangeon, Séverine; Duclos, Martine; Vorilhon, Philippe; Mermillod, Martial; Baker, Julien S.; Pereira, Bruno; Navel, Valentin (Sports medicine (Auckland), 2020)
Background Sedentary behaviour is a major risk of mortality. However, data are contradictory regarding the effects of active commuting on mortality. Objectives To perform a systematic review and meta-analysis on the effects of active commuting on mortality. Methods The PubMed, Cochrane Library, Embase, and Science Direct databases were searched for studies reporting mortality data and active commuting (walking or cycling) to or from work. We computed meta-analysis stratified on type of mortality, type of commuting, and level of commuting, each with two models (based on fully adjusted estimates of risks, and on crude or less adjusted estimates). Results 17 studies representing 829,098 workers were included. Using the fully adjusted estimates of risks, active commuting decreased all-cause mortality by 9% (95% confidence intervals 3–15%), and cardiovascular mortality by 15% (3–27%) ( p < 0.001). For stratification by type of commuting, walking decreased significantly all-cause mortality by 13% (1–25%), and cycling decreased significantly both all-cause mortality by 21% (11–31%) and cardiovascular mortality by 33% (10–55%) ( p < 0.001). For stratification by level of active commuting, only high level decreased all-cause mortality by 11% (3–19%) and both intermediate and high level decreased cardiovascular mortality. Low level did not decrease any type of mortality. Cancer mortality did not decrease with walking or cycling, and the level of active commuting had no effect. Low level walking did not decrease any type of mortality, intermediate level of walking decreased only all-cause mortality by 15% (2–28%), and high level of walking decreased both all-cause and cardiovascular mortality by 19% (8–30%) and by 31% (9–52%), respectively. Both low, intermediate and high intensities of cycling decreased all-cause mortality. Meta-analysis based on crude or less fully adjusted estimates retrieved similar results, with also significant reductions of cancer mortality with cycling (23%, 5–42%), high level of active commuting (14%, 4–24%), and high level of active commuting by walking (16%, 0–32%). Conclusion Active commuting decreases mainly all-cause and cardiovascular mortality, with a dose–response relationship, especially for walking. Preventive strategies should focus on the benefits of active commuting.